دراسة تحليلية للطراز المعماري للحرم المكي والاستفادة منه في استلهام تصميمات للعباية النسائية - محسن، عبير عبدالله حسنين (كلية الإمارات للعلوم التربوية, 2021)
The fashion designer resorts to the use of multiple sources of inspiration that help him generate new and innovative ideas commensurate with the nature of the society for which he is designed in addition to the economic and cultural level, and architecture is considered an important source of inspiration due to the details, decorations and colors it contains, especially Islamic architecture because of its achievement of purpose Functional and aesthetic in architectural styles, especially mosques because of their special character and spirituality that suggest to the designer many ideas, whether using lines, ornaments or colors. The research is concerned with quoting and drawing inspiration from the first mosque set for people (The Grand Mosque in Mecca), which was unique in this capacity in the Almighty saying: "The first house was placed for the people who were blessed, The current research problem is how to inspire designs for women's abayas that are inspired by the architectural style of the Grand Mosque in Mecca The research aims to benefit from the architectural and decorative style of the Grand Mosque in Mecca in reviving Islamic architecture. The research assumes that there are statistically significant differences between the proposed designs in achieving the functional and aesthetic side of the design. The importance of research shows the development of the skill of quoting and drawing inspiration from the various architectural arts. The research follows the descriptive, One of analytical and experimental approach to suit both approaches to the research the most important results of the research was the presence and statistically significant differences between the opinions of the arbitrators about the proposed designs, where the eighth design was with a quality factor of 94.44%, followed by the third designs with a quality factor of 92.50% and the ninth design received the lowest evaluations with a quality factor of 79.17% and One of the most important recommendations is to pay attention to the multiple sources of inspiration, especially Islamic architecture.
يلجأ مصمم الأزياء إلى الاستعانة بمصادر الإلهام المتعددة والتي تساعده على توليد أفكار جديدة ومبتكره تتناسب مع طبيعة المجتمع الذي يصمم له بالإضافة إلى المستوي الاقتصادي والثقافي وتعتبر العمارة مصدرا هام من مصادر الإلهام وذلك لما تحتويه من تفاصيل وزخارف والوان وخاصة العمارة الإسلامية لما تتميز به من تحقق الغرض الوظيفي والجمالي في الطرز المعمارية وخاصة المساجد لما لها من طابع خاص وروحانيات توحي للمصمم بالعديد من الأفكار سواء باستخدام الخطوط أو الزخارف أو الألوان ويختص البحث بالاقتباس والاستلهام من أول مسجد وضع للناس (الحرم المكي) والذي تفرد بهذه الصفة في قوله تعالي "أن أول بيت وضع للناس الذي ببكة مباركا" كما أنه تفرد أيضا بوجود الكعبة المشرفة وإقامة شعائر الحج والعمرة ويتميز الحرم المكي بتصميم معماري مميز يدعو إلى البحث في خطوطه المختلفة للاستلهام منها حيث تمثلت مشكلة البحث الحالي في كيفية استلهام تصميمات للعباية النسائية مستوحاة من الطراز المعماري للحرم المكي ويهدف البحث الاستفادة من الطراز المعماري والزخرفي للحرم المكي في إحياء العمارة الإسلامية. ويفرض البحث أنه توجد فروق ذات دلالة إحصائية بين التصميمات المقترحة في تحقيق الجانب الوظيفي والجانب الجمالي للتصميم. وتظهر أهمية البحث في تنمية مهارة الاقتباس والاستلهام من فنون العمارة المختلفة ويتبع البحث المنهج الوصفي التحليلي والتجريبي لملائمة كلا المنهجين للبحث وكانت من أهم نتائج البحث وجود فروق ذات دلالة إحصائية بين أراء المحكمين حول التصميمات المقترحة حيث كان التصميم الثامن بمعامل جوده 94.44% ويليه التصميمات الثالث بمعامل جودة 92.50% وحصل التصميم التاسع على أقل التقييمات بمعامل جودة 79.17 % ومن أهم التوصيات الاهتمام بالمصادر المتعددة للإلهام وخاصة العمارة الإسلامية.
Keywords: تصميمات الأزياء -- العبايات النسائية -- الوحي والإلهام -- العمارة الإسلامية -- الحرم المكي